2022
DOI: 10.1002/adfm.202204751
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Prussian Blue Analogs Boxes Inside Conducting Polymer Nanotubes Enables Significantly Enhanced Catalytic Performance for Water Treatment

Abstract: Tubular nanoreactor with unique void-confinement effect has captured great attention for catalytic applications but is challenging in controllable fabrication and realizing a synergistically enhanced performance. Herein, a template polymerization-guided synthetic strategy is presented to confine hollow Prussian blue analog boxes inside conducting polypyrrole nanotubes (H-CoFe PBA@PPy NTs) as efficient peroxymonosulfate activator toward catalytic oxidation of toxic organic contaminants. This delicately designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 90 publications
1
33
0
Order By: Relevance
“…Based on the above analysis, it can be suggested that the enhanced POD-like performance of the CuO/NiO NTs may have resulted from the following reasons. First, the tubular CuO/NiO NTs show an apparent hollow pore inside the material, which can serve as the main diffusion channel for molecules and endow a desirable mass transfer of reactants to achieve a promoted catalytic property, which is in accordance with previous reports. ,, Second, the good affinity between the CuO/NiO NTs and TMB substrate benefits us to promote the catalytic activity, which is confirmed by the above kinetic result of a low K m value toward TMB (Figure ). Third, the heterogeneous structure composed of NiO and CuO facilitates the electron transfer from the catalyst to the H 2 O 2 , promoting the POD-like activity, which is proven by the above electrochemical analysis (Figure S4b).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Based on the above analysis, it can be suggested that the enhanced POD-like performance of the CuO/NiO NTs may have resulted from the following reasons. First, the tubular CuO/NiO NTs show an apparent hollow pore inside the material, which can serve as the main diffusion channel for molecules and endow a desirable mass transfer of reactants to achieve a promoted catalytic property, which is in accordance with previous reports. ,, Second, the good affinity between the CuO/NiO NTs and TMB substrate benefits us to promote the catalytic activity, which is confirmed by the above kinetic result of a low K m value toward TMB (Figure ). Third, the heterogeneous structure composed of NiO and CuO facilitates the electron transfer from the catalyst to the H 2 O 2 , promoting the POD-like activity, which is proven by the above electrochemical analysis (Figure S4b).…”
Section: Resultssupporting
confidence: 87%
“…The effect of the pH of the reaction system on the POD-like catalytic activity is also investigated, presenting the highest POD-like activity at pH = 4.0 (Figure b), which might be attributed to the improved interactions between the CuO/NiO NTs and POD-like substrates under such conditions in accordance with previous reports. In addition, we have explored the POD-like activities of CuO/NiO NTs with varied feeding contents of the copper precursor, demonstrating the best catalytic property of the CuO/NiO-3 NTs (Figure c,d). Furthermore, the prepared CuO/NiO NTs have also shown better POD-like activity than the single-component samples, which is 13.2-fold and 4.2-fold as high as that of bare CuO and NiO catalysts, implying that a synergy between the two components is achieved from an efficient electron transfer between NiO and CuO and fast mass transportation in the tubular channel. , Subsequently, the durability and recyclability of the obtained CuO/NiO NTs are investigated, presenting an almost unchanged POD-like activity for about two weeks in durability and a POD-like activity of 89.5% after five cycles, indicating a desirable storage stability and superior recyclability property of the catalyst (Figure S3).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…[30][31][32][33] Electrospinning technology is a facile method to fabricate one-dimensional (1D) elongated carbon-based materials with large aspect ratios, high electrical conductivity, tunable compositions and morphologies, and has been broadly used in a variety of electrocatalytic reactions. [34][35][36][37] Herein, based on the above concepts, we adopt a novel electrospinning-carbonization-oxidation process to construct a highly efficient bifunctional catalyst in which partially oxidized Ru nanoparticles are embedded within the 1D carbon nanofibers (RuO 2 /Ru-CNFs). Owing to the configuration of the heterostructure between RuO 2 and metallic Ru as well as the favorable electrical conductivity of the CNFs, the obtained RuO 2 /Ru-CNF catalyst only requires low overpotentials of 203 mV for the OER and 21 mV for the HER at 10 mA cm −2 in 1 M KOH.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figures S8 and a, individual Fe 2 O 3 NFs and bare Fe NPs exhibit negligible catalytic activity, whereas a significantly enhanced POD-like activity is achieved after encapsulating them in NC NTs. Additionally, the unsatisfactory catalytic activity of bare NC NTs further demonstrates the significant role of the confined structure of Fe NPs inside NC NTs, which might be attributed to the concentration of the reactive molecules and the promoted electron/mass transport property in the confined structure. , To deeply understand the catalytic mechanism of Fe@NC NTs, the generated active intermediates are identified by electron paramagnetic resonance spectroscopy (EPR) tests utilizing 5-dimethyl-1-pyrroline- N -oxide (DMPO) as a spin trapping agent. It is seen that there are much weaker signals appearing in the DMPO + H 2 O 2 system, while the signals of DMPO– • OH are significantly enhanced after the addition of the Fe@NC NTs catalyst.…”
Section: Resultsmentioning
confidence: 64%